Supplementing Substance Use Prevention With Sexual Health Education: A Partner-Informed Approach to Intervention Development. Issue 1 (January 2022) - Powell, Terrinieka W.; Jo, Meghan; Smith, Anne D.; Marshall, Beth D.; Thigpen, Santha; Offiong, Asari; Geffen, Sophia R.
Supplementing substance use prevention with sexual health education would allow educators to address the risk and protective factors that influence both health issues. This streamlined approach may minimize the inefficiencies of multisession, single-purpose interventions. Our team developed a supplemental sexual and reproductive health (SRH) unit to align with an existing evidence-based intervention, LifeSkills Training (LST). This goal of this article is to describe our process, final product, lessons learned, and future directions. Our partner-informed approach took place across three key phases: (1) formative insights, (2) unit development, and (3) pilot implementation. The final supplemental SRH unit is ten, 45-minute sessions offered to seventh- and eighth-grade students and includes a set of learning objectives that are aligned with individual sessions. The supplemental SRH unit also mirrors existing LST modules in length, flow, layout, facilitator instructions, focus on prevention, and utilization of a student workbook. Lessons learned include strategies to effectively incorporate a wide range of ongoing feedback from multiple sources and quickly respond to staff turnover. This partnership approach serves as a model for researchers and practitioners aiming to extend the reach of existing evidence-based programs.